Pengembangan Sistem Layanan Minibank untuk Mendukung Badan Layanan Umum Daerah (BLUD) DI SMKN SURABAYA - Yulius Hari; Darmanto Darmanto; Melvie Paramitha; Minny Elisa Yanggah (UN PENMAS (Jurnal Pengabdian Masyarakat untuk Negeri), 2023)
Through Law No. 20/2003 on the national education system, Article 48 has become the foundation for the development of the Regional Public Service Agency (BLUD), which was then transformed into a development for vocational education units. SMK BLUD is an institution established by the local government to manage and provide educational facilities for SMK students. The partner of this service activity, SMKN Surabaya, is also required to immediately develop BLUD so that it can develop financial independence and develop educational facilities through self-help. Partners in developing BLUD managed all transactions are also run through the school's Minibank which is also one of their BLUDs. With the development of this minibank, it is necessary to develop an information system that is able to assist partners in recording all administration and transaction flows that occur in this BLUD. This is where this community service activity is carried out, in helping to realize a system that supports BLUD Minibank, especially for partners. The result of this community service activity is the optimization of efficiency in BLUD minibank transactions, as well as the escalation of partner capabilities in the use of information technology.